PERSEPSI REMAJA TERHADAP KEKERASAN DALAM TAYANGAN OPERA VAN JAVA (OVJ) : STUDI KASUS DI KELURAHAN TANGKERANG UTARAKECAMATAN BUKIT RAYA KOTA PEKANBARU - Evelin, Yuyun; Nasution, Belli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this study is to find out what forms of violence that often occurs in Opera Van Java (OVJ) Show and find out how adolescent perceptions of violence in Opera Van Java (OVJ) in the North Tangkerang District of Bukit Raya Pekanbaru.This study used a qualitative descriptive approach, namely measurement of certain social phenomena descriptively. In this study, researchers used the informant through key person. The data were analyzed qualitatively is the response of adolescents about violence that occurred in Opera Van Java (OVJ) Show at Trans7 Station.OVJ show can shape the cultures of violence. This means that the television is able to break through into the souls of children and adolescents in applying what they get from television in everyday life. The violence in OVJ Show can influences the behavior of children and adolescents. They can be affected in a positive direction or a negative direction depending on the child or adolescent individually. OVJ Show on Trans 7 affects children and adolescents because of the ability to create the impression and perception that a charge in tv show to becomes more real so they want to try what they see on the television to be referred to as the jocks in their environment.Keywords: Perception, Teen, Violence, OVJ Show